Aplikasi dan Evaluasi Teknik untuk Mengurangi Tingkat Putus Sekolah pada Awal Tutor - Rafael Alfonso Figueroa Díaz; Pablo Alberto Limón Leyva; Erica Cecilia Ruiz Ibarra (Journal of Education and Teaching (JET), 2024)
In the current university environment, national accreditations within the field of engineering serve as a continuous improvement tool for educational programs. These accreditations contribute to increased completion rates and a reduction in school dropout rates, underscoring the utility of tutoring throughout the educational process. High school students adapting to the new pace of university work often undergo significant changes in their school performance habits. Therefore, the initial group tutoring sessions aim to address issues and undertake specific activities that help students learn about their attending university, its organization and work areas, the program they are enrolled in, and the need for psychological support and specialized counseling, among other elements. This work presents an analysis and evaluation of the application of a technique designed to reduce dropout rates in Tutoring 1 for first-semester engineering students.